Design of Wastewater Filtration System for ‎Microcontroller and Smartphone-Based Hydroponic ‎Agriculture - Ilham Dwi Puspita Candra; Imam Taufik; Trinil Muktiningrum (PT FORMOSA CENDEKIA GLOBAL, 2022)
The level of water pollution sourced from daily household waste needs to be watched out, especially ‎since the level of awareness of the Indonesian people is still relatively low in water treatment. Waste water ‎treatment plants are always synonymous with high installation costs and the complexity of maintenance and ‎management of the installation equipment.‎ Based on the above background, the authors make a household wastewater treatment installation ‎device in the Lirboyo Al-Mahrusiyah Islamic Boarding School Dormitory, Kediri City, into ready-to-use water ‎for urban agriculture using the hydroponic system method. This device is based on a microcontroller that is ‎connected to the Blynk Web Server which can be operated using a Smartphone. This system is also able to provide results of monitoring the quality of water quality standards resulting ‎from waste treatment in the Lirboyo Al-Mahrusiyah Islamic Boarding School Dormitory. This application can ‎also be applied as a remotecontrol tool by utilizing the internet network to determine the quality of household ‎wastewater quality standards with a water acidity level (pH) of 7.12 and a TDS (Total Dissolve Solid) value of ‎‎521 mg/L and turbidity of 5 NTU (Nephelometric Turbidity Units) in real time.‎